Design and Build Solar Panels as Source Rice Thresher Motor Energy - Sitepu, Trahman; Malau, Ayu Tamara; Cholish, C; Abdullah, A (Institute for Research and Community Service, Universitas Malikussaleh, Indonesia, 2021)
Renewable energy generated from sunlight (Solar Panels) can be formed as alternative energy that can be applied to a source of electrical energy in rice thresher equipment. The use of solar energy with a power of 240 WP through the object on the rice thresher is able to replace the rice thresher automatically which is more effective. The power generated by solar energy will be processed into a charging source for the Regulated Battery Charger which can be supplied at a voltage to the control circuit to drive the DC motor. The average voltage generated by solar energy is 0.000394 volts/lux with a maximum voltage of 36.2 volts and a DC motor of 350 watts. In addition, the speed of this rice thresher is 950.8 rpm and is able to produce very good rice cutting against the designed solar energy capabilities.